Perceptions of Study Conditions and Depressive Symptoms During the COVID-19 Pandemic Among University Students in Germany: Results of the International COVID-19 Student Well-Being Study - Matos Fialho, Paula Mayara; Spatafora, Franca; Kühne, Lisa; Busse, Heide; Helmer, Stefanie M.; Zeeb, Hajo; Stock, Christiane; Wendt, Claus; Pischke, Claudia R. (Frontiers in Public Health, 2021)
Background: Results of previous studies examining the impact of the SARS-CoV-1 epidemic in 2003 on university students’ mental well-being indicated severe mental health consequences. It is unclear how the current COVID-19 pandemic and the changes in study conditions due to federal regulations affected mental well-being in the German student population. We examined university students’ perceptions of study conditions during the COVID-19 pandemic and investigated associations between study conditions and depressive symptoms. Methods: A cross-sectional online survey was conducted in Germany in May 2020 at four universities (N=5,021, 69% female, mean age: 24 years, SD: 5.1). Perceived study conditions, as well as sociodemographic information, were assessed with self-generated items and the CES-D 8 scale was used to determine depressive symptoms. Associations between perceived study conditions (academic stress and academic satisfaction), in general, and confidence to complete the semester, in particular, and depressive symptoms were analyzed using generalized linear regressions. Results: Fifty-four percent of survey participants felt that the university workload had significantly increased since the COVID-19 pandemic; 48% were worried that they would not be able to successfully complete the academic year; 47% agreed that the change in teaching methods caused significant stress. Regarding depressive symptoms, the mean score of the CES-D 8 scale was 9.25. Further, a positive association between perceived study conditions and depressive symptoms was found (p<0.001), indicating that better study conditions were associated with fewer depressive symptoms. Results of the generalized linear regression suggest that better student mental well-being was related to higher confidence in completing the semester. Conclusions: This study provides first insights into perceived study conditions and associations with depressive symptoms among students during the COVID-19 pandemic in Germany. Findings underline the need for universities to provide intervention strategies targeting students’ mental wellbeing during the course of the pandemic.